How geo-strategy, warfare and war-tech have changed in 2022: A review of events which shaped the new paradigms of warcraft - Dhakate, Shaurya (U.S.I. Journal)
The year 2022 arrived with fresh opportunities and challenges for the world, transforming the way nations dealt with each other in the process of safeguarding their interests. The article looks back at the year to see how nations behaved in conflicts, what new strategic challenges emerged, and the development of new state of the art war-tech. It attempts to look at the events based on the level of significance they hold pertaining to the change in the global order, including territorial disputes, cyber warfare, war and recent development of war-tech. It concludes with the significant changes in the belief system around the world when it comes to how wars will be fought in the near future. These changes are a result of the paths that nations took in 2022 to gain strategic advantage over their adversaries.- Reproduced